Product innovation by Adidas Group through Sustainability - Crasto, Sheryl George; Kee, Daisy Mui Hung; Huan, Alyssia The Yi; Xin, Chen Woan; Juin, Hoon Xian; Man, Lau Kiew; Pandey, Divya (Journal of The Community Development in Asia, 2020)
Innovation is at the core of all products at Adidas. The Adidas group has toiled through the years to be the sole giant to manufacture and supply world-class sports products in their clothing, footwear, and accessories. The ongoing global climate change concerns and an intention to support the initiatives by various groups to protect the environment, the Adidas group shifted towards sustainability. The decision of re-considering materials while being manufactured was key to determine the innovation in their products through sustainability. The objective of the study is to understand the product innovation by Adidas by adopting sustainability and how this approach has affected the customer’s perception and brand image.